Implementasi LoRa sebagai Media Komunikasi Data Tinggi Air pada Lahan Gambut - Harpawi, Noptin; Triyani, Yuli; Rahmawaty, Made; Rizki Saputra, Muhammad (Politeknik Caltex Riau, 2025)
Peatland Forest Fires pose a serious threat, particularly in Riau, which has 3.89 million hectares of peatland and is highly vulnerable during the dry season. These fires are difficult to control because the flames can spread beneath the dry surface of the soil. One preventive measure is real-time monitoring of the water table to maintain soil moisture. Long Range (LoRa) technology, with its long-range communication and low power consumption, is more effective than cellular-based IoT systems, which are limited in remote areas. This study developed a seven-hop LoRa multi-hop system to transmit data from remote areas to a cellular network via river routes without the need for expensive infrastructure. The solution is more efficient, offering a cost reduction of up to 96%-99% compared to other methods. The system will be applied at PT Rimba Mandau Lestari, Siak Regency, Riau, to replace the less effective manual monitoring approach. Testing results showed that the use of a Low Noise Amplifier (LNA) improved signal quality, achieving an average RSSI of -97.6 dBm and a Delivery Success Rate of 100%, with a delay of up to 12.36 seconds.